The estimation of cloud-to-ground Lightning discharges from satellite data; Korus 2004; V. 1 - Ershova T. V. (2004, 2004)
We review the data from observations of lightning obtained by the Microlab-1 satellite for summer season between 1995 to 1999. The Microlab-1 satellite equiped optical imaging sensor - Optical Transient Detector (OTD). The areas of investigations were southern Germany and Tomsk region (Russia). We compare the OTD data with Lightning Position And Tracking System (LPATS) reported cloud-to-ground strokes for southern Germany. We found the empirical relation between OTD data and LPATS data for flat parts in southern Germany and calculated the estimated cloud-to-ground strokes for Tomsk region.